Methanol versus acetic acid extract effects on chicken eggshell membrane protein concentration, visualization and antioxidative potential / Nur Wadhihah Latif ... [et al.] - Latif, Nur Wadhihah; Abdullah, Nur Rasyidah; Zulkepli, Nur Ayunie; Johari, Amin Saiff; Tarmizi, Nur Hazirah; Mokhtar, Norehan (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Eggshell membrane (ESM) is a fibrous microstructure located between the eggshell’s layers. ESM contains numerous protein constituents that serve its beneficial biological activities. Proteins such as ovalbumin, collagens, keratins, ovomucoid and ovocleidin-116 have been extracted from ESM. However, ESM is extremely insoluble in water and has poor stability. Solvents are often used in the extraction process; thus, this study aims to extract and compare the effect of methanol and acetic acid on proteins from chicken ESM. Findings from this study demonstrate differences in methanol compared to acetic acid in ESM protein extraction. ESM protein concentration from acetic acid (1.14 mg/ml) is slightly higher than methanol (1.01 mg/ml). The SDS-PAGE result shows both solvents can extract proteins from ESM with different bands intensity. Both solvents show moderate antioxidative activity compared to L-Ascorbic acid as a control in the FRAP assay. This study shows the potential of both solvents to extract and maintain the bioactivity of proteins from ESM. However, further purification and quantitative studies are needed to completely identify protein fragments isolated by both solvents to be used in future applications such as medicine, dentistry, and food industry.